Implementasi Public Relations dalam Meningkatkan Pelayanan Informasi Rumah Sakit Umum Daerah (RSUD) Tengku Sulung Kabupaten Indragiri Hilir - Rahmatang; TIka Mutia (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2022)
The purpose of this study was to determine the form of implementation of public relations activities in improving information services at the Tengku Sulung Regional General Hospital (RSUD). This study uses a descriptive method with a qualitative approach. Methods of collecting data through interviews, observation, and documentation. The results showed that: Tengku Sulung Regional General Hospital (RSUD) implemented a form of trust through socialization to the community. Submission of information to the public with good and clear interaction and communication. The information services provided by the Hospital are right on target. The Tengku Sulung Regional General Hospital (RSUD) provides and carries out socialization, especially about free treatment. as communicator, the PR of Tengku Sulung Hospital in providing information services is also clear and easy to understand by patients and the community and uses social media as an alternative media in conveying information.